Asiatic Acid Exhibits Anti-inflammatory and Antioxidant Activities against Lipopolysaccharide and d-Galactosamine-Induced Fulminant Hepatic Failure - Lv, Hongming; Qi, Zhimin; Wang, Sisi; Feng, Haihua; Deng, Xuming; Ci, Xinxin (Frontiers in Immunology, 2017)
Inflammation and oxidative stress are essential for the pathogenesis of fulminant hepatic failure (FHF). Asiatic acid (AA), which is a pentacyclic triterpene that widely occurs in various vegetables and fruits, has been reported to possess antioxidant and antiinflammatory properties. In this study, we investigated the protective effects of AA against lipopolysaccharide (LPS) and D-galactosamine (GalN)-induced FHF and the underlying molecular mechanisms. Our ﬁndings suggested that AA treatment effectively protected against LPS/D-GalN-induced FHF by lessening the lethality; decreasing the alanine transaminase (ALT) and aspartate aminotransferase (AST) levels, interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α production, malondialdehyde (MDA) formation, myeloperoxidase (MPO) level and reactive oxygen species (ROS) generation (i.e., H2O2, NO and O2-), and increasing the glutathione (GSH) and superoxide dismutase (SOD) contents. Moreover, AA treatment significantly inhibited mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathway activation via the partial induction of programmed cell death 4 (PDCD4) protein expressions, which is involved in inflammatory responses. Furthermore, AA treatment dramatically induced the expression of the glutamate-cysteine ligase modifier (GCLM) subunit, the glutamate-cysteine ligase catalytic (GCLC) subunit, heme oxygenase-1 (HO-1), and NAD (P) H: quinone oxidoreductase 1 (NQO1), which are largely dependent on activation of the nuclear factor-erythroid 2-related factor 2 (Nrf2) through the induction of AMP-activated protein kinase (AMPK) and glycogen synthase kinase-3β (GSK3β) phosphorylation. Accordingly, AA exhibited protective roles against LPS/D-GalN-induced FHF by inhibiting oxidative stress and inflammation. The underlying mechanism may be associated with the inhibition of MAPK and NF-κB activation via the partial induction of PDCD4 and upregulation of Nrf2 in an AMPK/GSK3β pathway activation-dependent manner.